M. Daukšos Postilės postpozicinių vietininkų ir jiems sinonimiškų prielinksninių konstrukcijų vartosena ir vertimo šaltiniai - Žilinskaitė, Eglė (Baltistica, 2004)
THE USE OF POSTPOSITIONAL LOCATIVES AND SYNONYMOUS PREPOSITIONAL CONSTRUCTIONS IN M. DAUKŠA’S POSTILLA AND THEIR TRANSLATIONThe article deals with the system of four postpositional locatives and synonymous prepositional constructions. The system of four postpositional locatives in Daukša’s Postilla is quite well represented. The Polish prepositional constructions of Wujek’s The Little Postilla are translated by using the illative, allative, inessive and adessive or Lithuanian prepositional constructions.The illative translates from Polish the prepositional constructions do + gen., w + acc, na + acc. The allative corresponds to do + gen., ku + dat., na + acc. and genitive (in Polish syntagmas the verb with the prefix do- + genitive). The latter use in Polish could determine the use of the genitive instead of the allative in Daukša’s Postilla, e.g. bępigái to priwéʃsimę 44313-14 ~ tedy ʃnádnie tego dowiedʒ́iemy 46334.The inessive corresponds to the Polish prepositional constructions w + loc. and na + loc. (rarely), the adessive is equivalent mostly to u + gen. In comparison with the rest of the postpositional locatives, the adessive in its traditional meaning ‘location’ is found more seldom because of its neutralization with the inessive and the allative.When denoting the final point, the directional prepositional construction ant + gen. as a synonym of the illative and the allative is a word-for-word translation from Polish prepositional construction.The rest of the prepositional constructions correlating with postpositional locatives correspond to different Polish prepositional constructions (the data is in the table). A definition of the influence of Wujek’s Postilla on Daukša’s translation is complicated in this case. Both the syntactic and semantic system of the Lithuanian language and the syntax of Wujek’s Postilla could have determined the use of these prepositional constructions.
Keywords: senieji raštai; Daukša; Postilė; postpoziciniai vietininkai